THE 90Sr CONCENTRATION IN SURFACE SEAWATERS OF JAPAN SEA - Muslim M. (JOURNAL OF COASTAL DEVELOPMENT, 2006)
Distribution of 90Sr concentrations in surface seawater of Japan Sea has been studied from 30 June2000 to 18 July 2000. The concentrations of 90Sr varied according to the stations position and didn’tshow correlation with temperature and salinity. Distribution and level of 90Sr concentrations wereinfluenced by any factors such as distance from the sources of radionuclides and water current. Thestrong system of Tsushima Warm Current System and Kuroshio branch Current System in the Japan Seaincreased the leaching of 90Sr from the bottom sediment. The results of this study were much lower thanthose of previous study, presumably due to 90Sr characteristic will decrease with time and in theenvironment, it becomes incorporated with calcium. However, data in 1990 increased dramatically aseffect of Chernobyl nuclear power plant accident.